The EMU Consolidation Game - or: Does 3.0 Really Mean 3.0? - Friedrich Heinemann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1998)
Within the economic profession, it is a widely held view that the fiscal criteria of the Maastricht treaty are arbitrary numbers without economic foundation. Much of this criticism seems to overlook an important aspect - the strategic dimension of the criteria. This paper focuses on one particular question out of this broad strategic complex: How do the criteria change the fiscal bargaining situation on the national level? For this purpose, a bargaining game between a national finance minister and an interest group over budget consolidation is designed. The purpose of this paper is twofold : On the one hand the analysis should contribute to a better understanding of the strategic effects of the fiscal criteria in the pre-EMU period. On the other hand it is to provide insights helpful for the construction of credible and strategically consistent debt limits in the time after the introduction of the Euro.
Keywords: H60; F33; D72; C78; 330; European Monetary Union; Convergence Criteria; Budget Consolidation; Boundary; Signalling; Conditionality; Europäische Wirtschafts- und Währungsunion; Haushaltskonsolidierung; Konvergenzkriterien; Signalling; Finanzpolitik; Interessenpolitik; Verhandlungen; Theorie